A comparative study of clinical profile of diabetic tuberculosis patients with non diabetic tuberculosis patients of outpatient department of tertiary healthcare centre - Chikhalikar, Prachi; Bansode, M. V.; Paritekar, Anita; Bafna , Varun (International Journal of Research in Medical Sciences, 2024)
Background: The global increase in type 2 DM is recognized re-emerging risk and challenge to TB control in India. TB-T2D association is again at the frontline of risk factors for TB, with an estimated worldwide population attributable fraction of 34.5%. T2D not only increases TB risk 3-fold, but also TB treatment failure including death. And prognosis of diabetic tuberculosis patients as compared to non diabetic ones is poorer. Methods: An comparative analytical study was done in microbiologically confirmed 50 diabetic and 50 non diabetic TB patients registered in RNTCP OPD of tertiary healthcare hospital who were followed up for 3 months. Results: In our study we found that elderly (above 65 age group) male diabetic patients were affected more with tuberculosis as compared to young patients and data was statistically significant. Extrapulmonary involvement was seen more in diabetic patients as compared to non diabetic patients. Radiologically diabetic tuberculosis patient showed predominantly lower lobe of lung involvement as oppose to non diabetic tuberculosis patients who showed upper lobe of lung involvement and data was statistically significant. Outcomes like Multidrug Resistance and prolonged sputum positivity after intensive phase treatment was seen more with diabetic tuberculosis patients but this was not statistically significant. Conclusions: Early screening of TB patients for DM and vice versa and early initiation of treatment will prevent unfavourable outcomes of these patients.